'There is violence across, in all arenas': listening to stories of violence amongst sexual minority refugees in Uganda. Issue 4 (20th April 2020) - McQuaid, Katie
ABSTRACT: This article examines the complex marginalisation and persecution faced by sexual minorities in the Democratic Republic of Congo and forced displacement into Uganda. It demonstrates the need to create space for the voices of sexual minorities within transitional justice, and to attend to the wider systems of violence occurring through conflict and in its aftermath, as they articulate how everyday sexuality-based violence intersects with wider political violence. This article thus calls for a more transformative gendered approach to transitional justice that goes beyond the legal to address deeply ingrained gendered hierarchies of exclusion and stigmatisation of non-heteronormative sexualities.